If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(6m + 5) = 25 Reorder the terms: -1(5 + 6m) = 25 (5 * -1 + 6m * -1) = 25 (-5 + -6m) = 25 Solving -5 + -6m = 25 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -6m = 25 + 5 Combine like terms: -5 + 5 = 0 0 + -6m = 25 + 5 -6m = 25 + 5 Combine like terms: 25 + 5 = 30 -6m = 30 Divide each side by '-6'. m = -5 Simplifying m = -5
| x-4/5=x/9 | | 7-n=9 | | 12/60=1 | | 2(x+6)=3x | | y+3/7=y-3/4 | | 6(v+2)=2(8+2v) | | 17(12x-48)=-5100 | | -5(4x-3)= | | 6x+5=89-x | | -10.5q+1.4=-53.2-1.4q | | -6(6m+5)=25 | | 5=y/12 | | 0.4x=4 | | 7x+2/6=2x+7/3 | | 17+3x=5x+9 | | 2x+10=x-15 | | (m-4)(m-3)=0 | | 6-7(m-3)=1 | | (3m+7)(2m-1)= | | 4w+2x=7y | | (3x-3)(x^2-x-8)= | | 10x^3=80 | | 5x+2y-z=-29 | | 5+15x=2+16x | | 2x-3/5=x+3/4 | | 17=2(2m+9) | | -4y+12=-2(4y+6) | | 6=3+5d-10 | | s^2-12s+32=0 | | (3x+1)+(3x+1)+(x+1)+(x+1)=24 | | 20=2a+3a | | 6f=4 |